World Association for the Advancement of Veterinary Parasitology (WAAVP) concept paper on the efficacy evaluation of parasite vaccines - Edwin Claerebout; Damer P. Blake; Marshall W. Lightowlers; Terry W. Spithill; Santiago Nava; Ala E. Tabor; Anja Joachim; Ray M. Kaplan; Silvina Fernandez; Livio Costa Junior; Thomas Geurden (Veterinary Parasitology, 2026)

Little difference in the carbon balance of ryegrass/white clover- and plantain-dominated swards under dairy grazing - A. M. Wall; D. I. Campbell; S. Ray; J. P. Goodrich; L. A. Schipper (Nutrient Cycling in Agroecosystems, 2026)
Incorporating plantain into grazed pasture swards is proposed as an approach to reduce nitrate leaching and nitrous oxide emissions. However, consideration must be given to potential emission-swapping, such as a reduction in soil carbon (C), which can contribute to increases in atmospheric CO 2 . We compared the net ecosystem C balance (NECB) of two adjacent newly-sown paddocks (~ 3 ha each) of (i) traditional ryegrass and white clover pasture (RyWC) and (ii) a pure plantain sward, to assess whether plantain was beneficial or detrimental for the carbon balance. The NECB was calculated by combining eddy covariance (EC) measurements of CO 2 with measurements and estimates of lateral C transfers. Concurrently, regular measurements of sward composition and properties were taken. During the approximately 2.5-year experiment, the RyWC sward had an NECB of −199 g C m −2 period −1 compared with −273 g C m −2 period −1 for the plantain sward. The slightly larger loss from the plantain sward was attributed to lower excretal C returns due to differences in grazing duration (13.9 days for the RyWC paddock, and 5.9 days for the plantain paddock) during the first year of grazing. In the second year, the grazing management of the two paddocks was the same, and the NECBs were comparable. Both pasture dry matter production and CO 2 uptake were similar between the swards, although the lower C content of the plantain resulted in smaller C exports by either harvest or grazing. We conclude that small differences in NECB (and assumed soil C) between a pure plantain sward and a traditional ryegrass and white clover sward are associated with management rather than pasture species.

Despite warming temperatures, hatchery origin Chinook and coho salmon spawn earlier in the fall: a multi-decade analysis - Thomas P. Quinn; Jason Ray; Michael D. Tillotson (Hydrobiologia, 2026)

Challenges and Opportunities for Strengthening Bottom‐Tow Fisheries Sustainability - Suresh A. Sethi; Robert D. Murphy; Matthew R. Baker; Anita C. Kroska; Haraldur A. Einarsson; Owen S. Hamel; Shelton J. Harley; Pingguo He; James Ianelli; Stan Kotwicki; Robert A. McConnaughey; Chris McGonigle; et al. (Fish and Fisheries, 2026)
Bottom‐tow gear fisheries (trawls and dredges) produce ~24 million mt of harvest annually, representing a globally important animal‐sourced food system. While many are currently sustainably managed, growing concern over the potential for ecosystem impacts from bottom‐tow gears has increased pressure to improve these fisheries. We assembled an international working group of > 30 contributors, including fishing industry participants, managers, non‐governmental ocean conservation organization representatives, and scientists to synthesize obstacles to bottom‐tow fisheries sustainability and to develop expert‐based recommendations to operationalize sustainability advancements moving forward. We identified 30 key gaps impeding bottom‐towed fisheries sustainability spanning 6 core challenge areas including: seafloor disturbance, bycatch and discards, management design and implementation, fishing operations, cross‐sector conflicts, and public perception and communication. We generated 28 priority recommendations to address bottom‐tow fisheries sustainability obstacles with themes including: addressing data gaps, advancing mechanistic understanding and modelling tools, strengthening management processes, and improving knowledge sharing and communication. Cross‐disciplinary and diverse system experience among fisheries and marine ecosystem stakeholders will be critical for operationalizing bottom‐tow fisheries sustainability advancements. As the global human population approaches 10 bn in the next 30 years, ensuring sustainable wild capture fisheries is an imperative for feeding the world. Outputs from this synthesis serve as a resource for fishing and marine ecosystem stakeholders to identify key challenge areas and associated entry points for solutions‐oriented efforts to improve the sustainability of bottom‐tow fisheries.

Evaluating surface fluxes in WRF using eddy-covariance flux measurements in the Western and Eastern U.S. - Fan Wu; Kenneth J. Davis; Li Zhang; Ray G. Anderson; Jason P. Horne; Sarah Goslee; William Munger; Chenxia Cai; Yu Yan Cui; Zhan Zhao; Min Zhong (Agricultural and Forest Meteorology, 2026)

Geochemical evolution of geothermal waters in Trans-Himalayas: Implications for critical mineral deposition - Archisman Dutta; Parashar Mishra; Abhijit Mukherjee; Vivek P. Malviya; Sanjeet Kumar Verma; P.K. Singh; Biswajit Ray (Geochemistry, 2025)

Ecological harshness cues modulate food preferences and visual attention: An eye-tracking study - Ray Garza; Dariela Galindo; Karla P. Garcia; Tiffany Gutierrez (Food Quality and Preference, 2025)

NCBI Orthologs: Public Resource and Scalable Method for Computing High-Precision Orthologs Across Eukaryotic Genomes - Dong-Ha Oh; Alexander Astashyn; Barbara Robbertse; Nuala A. O’leary; W. Ray Anderson; Laurie Breen; Eric Cox; Olga Ermolaeva; Robert Falk; Vichet Hem; J. Bradley Holmes; Patrick Masterson; et al. (Journal of Molecular Evolution, 2025)
Orthologs are fundamental for enabling comparative genomics analyses that further our understanding of eukaryotic biology. The unprecedented increase in the availability of high-quality eukaryotic genomes necessitates scalable and accurate methods for orthology inference. The National Center for Biotechnology Information (NCBI) developed “NCBI Orthologs”, a resource and a computational pipeline designed to meet this challenge within the NCBI RefSeq framework. This system integrates protein similarity, nucleotide alignment, and microsynteny to achieve high-precision ortholog assignments across diverse eukaryotes. The pipeline leverages high-quality RefSeq annotations and processes genomes individually, ensuring scalability. Resulting ortholog data, organized into gene-level anchored sets, enables propagation of functional annotation information and facilitates comparative genomics. Critically, these data are integrated into the NCBI Gene resource, providing users with access from various entry points. The NCBI Datasets resource provides an intuitive interface to explore orthologous relationships on the web and allows bulk data download via the web, command-line tools, and an API. We detail the methodology, including anchor species selection and the decision tree used to arrive at high-confidence one-to-one orthology relationships. NCBI Orthologs is a valuable resource for facilitating functional annotation efforts and enhancing our understanding of eukaryotic gene evolution.

Periodic cropping of pasture for summer-grazed turnips leads to substantial carbon loss - Aaron M. Wall; Jordan P. Goodrich; Seager Ray; David I. Campbell; Louis A. Schipper (Agricultural and Forest Meteorology, 2025)

The teat skin microbiota of organic primiparous dairy cows is dynamic during the transition period - C.J. Dean; T. Ray; F. Peña-Mosca; T.J. Wehri; K. Sharpe; A.M. Antunes; E. Doster; L. Fernandes; V.F. Calles; C. Bauman; B. Heins; P. Pinedo; et al. (Preventive Veterinary Medicine, 2025)

Depth-dependent azimuthal seismic anisotropy governed by Couette/Poiseuille flow partitioning in the asthenosphere - Zhirui Ray Wang; Clinton P. Conrad; Sergei Lebedev; Giampiero Iaffaldano; John R. Hopper (Earth and Planetary Science Letters, 2025)

Seaweed extract-based biostimulants alleviate nutrient stress and enhance productivity and grain quality of wheat through efficient use of fertilizers nutrients under sub-optimal NPK application - Bijan Kumar Mondal; Abir Dey; M. C. Meena; Debarup Das; Archana Singh; Shivani Nagar; Prasenjit Ray; P. K. Upadhyay; Deepak Bamel; Amit Kumar Dash; Krishna Kumar Mourya; Narender Yadava; et al. (Journal of Applied Phycology, 2025)

Complete mitochondrial DNA genome of the Indian Chhattisgarh duck and its phylogenetic analysis - Rajni Kumari; Ratna Prabha; Tirupati Rao Golla; P. K. Ray; Reena Kamal; Jaipal S. Choudhary; Abhay Kumar; Sanjay Kumar; Shanker Dayal; P. C. Chandran; Jyoti Kumar; M. K. Tripathi; et al. (Journal of Genetics, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Simultaneous Drought and Heatwave Events During Austral Summer in Northeast Brazil - Katyelle F. S. Bezerra; Helber B. Gomes; Hakki Baltaci; Pallav Ray; Janaíına P. Nascimento; Dirceu L. Herdies; Matheus J. A. Lyra; Maria Cristina L. Silva; Fabrício D. S. Silva; Cláudio M. Santos e Silva; Heliofábio B. Gomes (International Journal of Climatology, 2025)
The simultaneous occurrence of heatwaves and droughts is becoming more frequent and intense under climate change, particularly affecting vulnerable regions like Northeast Brazil (NEB). This study presents a comprehensive assessment of these compound extremes using long‐term in situ observations and ERA5 reanalysis. Heatwaves were defined by daily temperatures exceeding the 90th percentile, and droughts by the standardised precipitation index (SPI‐1). Results reveal substantial spatio‐temporal variability in these events, with sharp increases in frequency, duration, and intensity since the early 1990s–especially in 1998, 2006 and 2015, linked to La Niña and El Niño events. Atmospheric analyses showed positive temperature anomalies at 2 m, persistent negative specific humidity at multiple pressure levels, and contrasting circulation anomalies: positive flow at 850 hPa, negative at 500 hPa, and changes in divergence and vorticity. The semiarid region of the northeast was the most affected by drought, while the northeastern coast had higher frequencies of heatwaves, with longer durations. These findings highlight the complex interactions driving compound extremes in NEB and underscore the urgent need for regional adaptation and mitigation strategies.

In silico exploration of pyrocannabinoid interactions with key protein targets - Giovanni A. Ramirez; Tesfay T. Tesfatsion; Monica K. Pittiglio; Kyle P. Ray; Andrew Westerkamp; Westley Cruces (In Silico Pharmacology, 2025)

Surface water quality under climate change scenarios in the Bosque watershed, Central Texas of United States - Gebrekidan Worku Tefera; Ram L. Ray; Vijay P. Singh (Ecohydrology & Hydrobiology, 2025)

Signal detection of ferric carboxymaltose-induced serious adverse events: disproportionality analysis of FAERS and VigiBase data and systematic review of case reports - Reddikumar Reddy Galigutta; Christy Thomas; Mahesh Rathod; P. N. Hasik; R. S. Ray; Jai Prakash; Krishna Undela (European Journal of Clinical Pharmacology, 2025)

Socio-economic impacts and responses of the fishing industry and fishery managers to changes in small pelagic fish distribution and abundance - Felipe J. Quezada-Escalona; Desiree Tommasi; Isaac C. Kaplan; Pierre-Yves Hernvann; Timothy H. Frawley; Dorleta Garcia; Leire Ibaibarriaga; Sonia Sánchez-Maroño; Carryn de Moor; Jennifer Beckensteiner; Amy M. Schueller; Diana Feijó; et al. (Reviews in Fish Biology and Fisheries, 2025)
Small Pelagic Fish (SPF) exhibit large fluctuations in abundance and distribution in response to environmental variability. To maintain the resilience of fishing communities and develop effective and equitable climate adaptation strategies, improved understanding of how the fishing industry responds to spatio-temporal shifts within and across SPF populations is of critical importance. In this paper, we examine the responses of the fishing industry and resource managers to shifts in SPF availability worldwide and identify the resulting socioeconomic impacts. Leveraging SPF case studies from around the globe, we synthesize and compare the social-ecological linkages and feedbacks mediating how SPF fisheries respond to changes in marine ecosystem structure and function associated with (1) spatial shifts in species distribution and habitat availability, (2) ‘boom and bust’ population dynamics, or (3) changes in fish size and quality. Our case studies illustrate multiple paths towards the resilience of small pelagic fisheries and the fishing industry dependent upon them while emphasizing the need for increased coordination and cooperation across sectors and scales as climate change progresses. Drawing from the lessons offered by historical responses, as environmental variability increases, efforts to increase the flexibility and dynamism of SPF harvest portfolios and management strategies, licensing regimes, and international catch and allocation agreements may be required to ensure resource sustainability and human well-being.

Equine welfare assessment skills certification course - R. Stewart; B. Wassel; A. Best; L. Ray; B. McGonagill; B. Jackson; P. Sapp; K. Duberstein (Journal of Equine Veterinary Science, 2025)

Correction: Antioxidant Effect of Naringin Demonstrated Through a Bayes’ Theorem Driven Multidisciplinary Approach Reveals its Prophylactic Potential as a Dietary Supplement for Ischemic Stroke - Manju Babu; Rajas M. Rao; Anju Babu; Jenat Pazheparambil Jerom; Anaekshi Gogoi; Nikhil Singh; Meenakshi Seshadri; Animikh Ray; Bhaskara P. Shelley; Arnab Datta (Molecular Neurobiology, 2025)

Advancing salinity and nutrient management for irrigation science - Davie M. Kadyampakeni; Ray G. Anderson; Michael P. Schmidt (Irrigation Science, 2025)

Impacts of N-(n-Butyl)thiophosphoric triamide (NBPT) on the physicochemical properties of milk protein isolate (MPI) dispersions: A study on micelle integrity - Maria P. Byrne; Patrick J. Forrestal; Tom F. O’ Callaghan; Niharika Rahman; Aishwarya Ray; Martin Danaher; Bernard M. Corrigan; Noel A. McCarthy; Chikere G. Nkwonta; Karl Richards; Farhad Garavand; Enda Cummins; et al. (Food Structure, 2025)

Antioxidant Effect of Naringin Demonstrated Through a Bayes’ Theorem Driven Multidisciplinary Approach Reveals its Prophylactic Potential as a Dietary Supplement for Ischemic Stroke - Manju Babu; Rajas M. Rao; Anju Babu; Jenat Pazheparambil Jerom; Anaekshi Gogoi; Nikhil Singh; Meenakshi Seshadri; Animikh Ray; Bhaskara P. Shelley; Arnab Datta (Molecular Neurobiology, 2025)

Molecular Characterization and Seasonal Variation in Expression of HSP70.1 Gene in Gangatiri Cattle and Its Comparison with Buffalo - Shanker Dayal; Birendra Kumar; Rajni Kumari; Jyoti Kumar; Pradeep Kumar Ray; P. C. Chandran; Amitava Dey (Biochemical Genetics, 2025)

Education for sustainable development (ESD) through participatory research (PR): A systematic review - Alexa Ray R. Fernando; Gizelle P. Tajan (Journal of Cleaner Production, 2024)

Simultaneous folate fortification and pesticide residue degradation in finger millet (Eleusine coracana) via malting and Lactiplantibacillus plantarum-mediated fermentation - Priyadarshini P. Nayak; Rudra P. Das; Sachin K. Mahanta; Abhishek Singh; Ajit K. Dhal; Rajani Kanta Mahapatra; Luna Goswami; Lopamudra Ray; Sunil K. Behera; Elna M. Buys; Sandeep K. Panda (Food Bioscience, 2024)

Lactic acid bacteria in the functional food industry: biotechnological properties and potential applications - Md Minhajul Abedin; Rounak Chourasia; Loreni Chiring Phukon; Puja Sarkar; Ramesh C. Ray; Sudhir P. Singh; Amit Kumar Rai (Critical Reviews in Food Science and Nutrition, 2024)

Advanced Numerical Simulation of Scour around Bridge Piers: Effects of Pier Geometry and Debris on Scour Depth - Muhanad Al-Jubouri; Richard P. Ray; Ethar H. Abbas (Journal of Marine Science and Engineering, 2024)
Investigating different pier shapes and debris Finteractions in scour patterns is vital for understanding the risks to bridge stability. This study investigates the impact of different shapes of pier and debris interactions on scour patterns using numerical simulations with flow-3D and controlled laboratory experiments. The model setup is rigorously calibrated against a physical flume experiment, incorporating a steady-state flow as the initial condition for sediment transport simulations. The Fractional Area/Volume Obstacle Representation (FAVOR) technique and the renormalized group (RNG) turbulence model enhance the simulation’s precision. The numerical results indicate that pier geometry is a critical factor influencing the scour depth. Among the tested shapes, square piers exhibit the most severe scour, with depths reaching 5.8 cm, while lenticular piers show the least scour, with a maximum depth of 2.5 cm. The study also highlights the role of horseshoe, wake, and shear layer vortices in determining scour locations, with varying impacts across different pier shapes. The Q-criterion study identified debris-induced vortex generation and intensification. The debris amount, thickness, and pier diameter (T/Y) significantly affect the scouring patterns. When dealing with high wedge (HW) debris, square piers have the largest scour depth at T/Y = 0.25, while lenticular piers exhibit a lower scour. When debris is present, the scour depth rises at T/Y = 0.5. Depending on the form of the debris, a significant fluctuation of up to 5 cm was reported. There are difficulties in precisely estimating the scour depth under complicated circumstances because of the disparity between numerical simulations and actual data, which varies from 6% for square piers with a debris relative thickness T/Y = 0.25 to 32% for cylindrical piers with T/Y = 0.5. The study demonstrates that while flow-3D simulations align reasonably well with the experimental data under a low debris impact, discrepancies increase with more complex debris interactions and higher submersion depths, particularly for cylindrical piers. The novelty of this work lies in its comprehensive approach to evaluating the effects of different pier shapes and debris interactions on scour patterns, offering new insights into the effectiveness of flow-3D simulations in predicting the scour patterns under varying conditions.

Single-crystal 40Ar/39Ar dating of the Montagna Grande-Monte Gibele trachytic shield volcano, Pantelleria (Strait of Sicily rift zone), Italy - John C. White; Daniel P. Miggins; Ray Macdonald (Geochemistry, 2024)

A test of trade-offs in dispersal and reproduction within and between a sister species pair of specialist insect herbivores - Amy M. Roush; Linyi Zhang; Glen Ray Hood; James R. Ott; Scott P. Egan (Oecologia, 2024)

Geochemistry of volcanic glass from Mahanadi offshore region, eastern continental margin of India: Constraints on the contribution of latest Toba super-eruption - Muralidhar Kocherla; Durbar Ray; Manavalan Satyanarayanan; Hilda Joao; Virsen Gaikwad; P. B. Ramamurty (Acta Oceanologica Sinica, 2024)

Fruit waste-derived cellulose-polyaniline composite for adsorption-coupled reduction of chromium oxyanions - Pratiksha Joshi; Sweta Mehta; Ramesh N. Goswami; Manoj Srivastava; Anjan Ray; Om P. Khatri (Environmental Science and Pollution Research, 2024)

HydroShare retrospective: Science and technology advances of a comprehensive data and model publication environment for the water science domain - David G. Tarboton; Daniel P. Ames; Jeffery S. Horsburgh; Jonathan L. Goodall; Alva Couch; Richard Hooper; Jerad Bales; Shaowen Wang; Anthony Castronova; Martin Seul; Ray Idaszak; Zhiyu Li; et al. (Environmental Modelling & Software, 2024)

Fentanyl Exposure and Detection Strategies Utilized by Clinical Trial Participants Seeking Linkage to Opioid Use Disorder Treatment at a Syringe Service Program - Dennis P. Watson; Bradley Ray; Peter Phalen; Sarah E. Duhart Clarke; Lisa Taylor; James Swartz; Nicole Gastala (Journal of Medical Toxicology, 2024)
Introduction The USA continues to face a fentanyl-driven overdose epidemic. Prior research has demonstrated users of illicit opioids are concerned about fentanyl exposure and overdose, but the strategies they report using to detect fentanyl’s presence lack empirical support. This study compares self-report and biologically detected fentanyl use and investigates overdose risk and risk reduction behaviors among a sample of high-risk people who use opioids. Methods Structured enrollment interviews conducted as part of a larger clinical trial assessed self-reported fentanyl exposure as well as strategies used to determine believed fentanyl exposure and prevent overdose among 240 participants enrolled at a Chicago, IL syringe service program. Urinalysis measured actual fentanyl exposure. Results Most participants identified as African American (66.7%) and had considerable overdose experience (76.7% lifetime and 48% in the past year). Most also tested positive for fentanyl (93.75%) despite reporting no past year use of fentanyl or fentanyl-adulterated drugs (64.17%). The most utilized approaches reported for identifying fentanyl exposure were stronger effects of the drug (60.7%), sight or taste (46.9%), and being told by someone using the same drugs (34.2%). Few participants (14%) reported using fentanyl test strips. No significant associations were identified between self-report and urinalysis measures or urinalysis results and risk reduction strategies. Conclusion This study adds to prior fentanyl exposure risk research. The disconnect between participants’ fentanyl detection methods and reported overdose experiences supports the need for more research to identify and understand factors driving access and use of overdose prevention resources and strategies.

Cytoskeletal Remodeling and Gap Junction Translocation Mediates Blood–Brain Barrier Disruption by Non-invasive Low-Voltage Pulsed Electric Fields - Neeraj Raghuraman Rajagopalan; William-Ray Vista; Masashi Fujimori; Laurien G. P. H. Vroomen; Juan M. Jiménez; Niranjan Khadka; Marom Bikson; Govindarajan Srimathveeravalli (Annals of Biomedical Engineering, 2024)

Negative δ13Ccarb excursions within early part of the Lomagundi event recorded in the Paleoproterozoic sedimentary carbonates, Aravalli Supergroup, Rajasthan India: Chemostratigraphy and basin evolution - Abhisikta Goswami; Shushanta Sarangi; Sarada P. Mohanty; Dattatray J. Patil; Anindya Sarkar; Jyoti S. Ray; Satyabrata Das; Debadutta Mohanty; S. Masood Ahmad; Rudra M. Pradhan; Arijit Barik (Precambrian Research, 2023)

Offsets in tide-gauge reference levels detected by satellite altimetry: ten case studies - R. D. Ray; M. J. Widlansky; A. S. Genz; P. R. Thompson (Journal of Geodesy, 2023)
Comparing measurements of absolute sea level by satellite altimetry and relative sea level by a tide gauge can reveal errors in either measurement system. Combining the measurements can determine vertical land motion (VLM) at the tide gauge. We here discuss ten case studies in which a tide gauge has likely experienced a small ( $$\le 10$$ ≤ 10 cm), discontinuous offset in the vertical, suggesting inadvertent loss of reference-level stability. Proper interpretation of offsets is helped if independent VLM measurements from nearby geodetic stations are available. In two cases, earthquake-induced VLM cannot be ruled out, although it appears unlikely. Offsets as small as 1–2 cm can be detected when both altimeter and tide gauge successfully observe the same ocean signal. This is most likely to occur for tide gauges located on small, open-ocean islands. Tide gauges near large land masses are typically more challenging owing to inadequacies of satellite altimetry near land and to differences between coastal and open-ocean sea levels. The case studies highlight the utility of satellite altimetry for tide-gauge quality control.

Experimental investigation of factors affecting the characterisation of soil strength properties using a Bevameter in-situ plate sinkage and shear test apparatus - Ray Kruger; P. Schalk Els; Herman A. Hamersma (Journal of Terramechanics, 2023)

Porewater and solid phase speciation geochemistry of phosphorus in the Western Bay of Bengal: An assessment of depositional pathways - P. Linsy; B. Nagender Nath; M.B.L. Mascarenhas-Pereira; Tyson Sebastian; B. Ramalingeswara Rao; Armoury Kazip; Durbar Ray; Saranya Jayachandran; L. Surya Prakash (Marine Geology, 2023)

The Ontology of Biological Attributes (OBA)—computational traits for the life sciences - Ray Stefancsik; James P. Balhoff; Meghan A. Balk; Robyn L. Ball; Susan M. Bello; Anita R. Caron; Elissa J. Chesler; Vinicius de Souza; Sarah Gehrke; Melissa Haendel; Laura W. Harris; Nomi L. Harris; et al. (Mammalian Genome, 2023)
Existing phenotype ontologies were originally developed to represent phenotypes that manifest as a character state in relation to a wild-type or other reference. However, these do not include the phenotypic trait or attribute categories required for the annotation of genome-wide association studies (GWAS), Quantitative Trait Loci (QTL) mappings or any population-focussed measurable trait data. The integration of trait and biological attribute information with an ever increasing body of chemical, environmental and biological data greatly facilitates computational analyses and it is also highly relevant to biomedical and clinical applications. The Ontology of Biological Attributes (OBA) is a formalised, species-independent collection of interoperable phenotypic trait categories that is intended to fulfil a data integration role. OBA is a standardised representational framework for observable attributes that are characteristics of biological entities, organisms, or parts of organisms. OBA has a modular design which provides several benefits for users and data integrators, including an automated and meaningful classification of trait terms computed on the basis of logical inferences drawn from domain-specific ontologies for cells, anatomical and other relevant entities. The logical axioms in OBA also provide a previously missing bridge that can computationally link Mendelian phenotypes with GWAS and quantitative traits. The term components in OBA provide semantic links and enable knowledge and data integration across specialised research community boundaries, thereby breaking silos.

SoJel –A 3D printed jellyfish-like robot using soft materials for underwater applications - Pawandeep Singh Matharu; Zhong Wang; John H. Costello; Sean P. Colin; Ray H. Baughman; Yonas T. Tadesse (Ocean Engineering, 2023)

Spatial and temporal variability in summertime dissolved carbon dioxide and methane in temperate ponds and shallow lakes - Nicholas E. Ray; Meredith A. Holgerson; Mikkel Rene Andersen; Jānis Bikše; Lauren E. Bortolotti; Martyn Futter; Ilga Kokorīte; Alan Law; Cory McDonald; Jorrit P. Mesman; Mike Peacock; David C. Richardson; et al. (Limnology and Oceanography, 2023)
Small waterbodies have potentially high greenhouse gas emissions relative to their small footprint on the landscape, although there is high uncertainty in model estimates. Scaling their carbon dioxide (CO 2 ) and methane (CH 4 ) exchange with the atmosphere remains challenging due to an incomplete understanding and characterization of spatial and temporal variability in CO 2 and CH 4 . Here, we measured partial pressures of CO 2 ( p CO 2 ) and CH 4 ( p CH 4 ) across 30 ponds and shallow lakes during summer in temperate regions of Europe and North America. We sampled each waterbody in three locations at three times during the growing season, and tested which physical, chemical, and biological characteristics related to the means and variability of p CO 2 and p CH 4 in space and time. Summer means of p CO 2 and p CH 4 were inversely related to waterbody size and positively related to floating vegetative cover; p CO 2 was also positively related to dissolved phosphorus. Temporal variability in partial pressure in both gases weas greater than spatial variability. Although sampling on a single date was likely to misestimate mean seasonal p CO 2 by up to 26%, mean seasonal p CH 4 could be misestimated by up to 64.5%. Shallower systems displayed the most temporal variability in p CH 4 and waterbodies with more vegetation cover had lower temporal variability. Inland waters remain one of the most uncertain components of the global carbon budget; understanding spatial and temporal variability will ultimately help us to constrain our estimates and inform research priorities.

Measurement of grass uptake of the urease inhibitor NBPT and of the nitrification inhibitor dicyandiamide co-applied with granular urea - Niharika Rahman; Chikere G Nkwonta; Martin Danaher; Karl G. Richards; Sean A Hogan; Enda Cummins; Macdara O’ Neill; Aishwarya Ray; Maria P. Byrne; Patrick J. Forrestal (Environmental Science and Pollution Research, 2023)

The demographic consequences of fertility reduction in rats and voles - Stephen M. Shuster; Brandy Pyzyna; Courtney Ray; Loretta P. Mayer (Journal of Pest Science, 2023)
Rodent population control is a global problem, complicated by evolved non-responsiveness to rodenticide treatment. Contraceptives could help mitigate this challenge, but questions remain about their efficacy, especially for rodenticide-resistant populations. We used an age-dependent demographic model to generate two hypotheses: Fertility reduction applied early in female lifetimes (1) is more effective in controlling rodent populations than when applied later in female lifetimes, and (2) is effective in controlling rodent populations that are expanding. Compared to controls, fertility reduction applied early, in mid-life, and late in female lifetimes, decreased, matched, and accelerated, respectively, the rates of population growth. Fertility reduction was effective in reducing population size only when sustained over multiple generations and was ineffective when application was episodic. Substituting classic Rattus norvegicus and Microtus agrestis life history data into our simulation framework confirmed that early fertility reduction was effective in controlling population growth, including expanding populations in both species. These simulations generated two additional hypotheses for field applications of fertility control: Over treatment durations, (3) the fraction of the population consisting of juveniles, and (4) the overall population size, will both decrease. We tested these predictions using a 12-month contraceptive bait application on rats in two urban US locations (Washington, DC) where rodenticides were already deployed. Consistent with our predictions, these populations showed marked decreases in the proportion of juvenile to adult rats, and in the total number of rats observed in camera traps over the study period. Our results support fertility control as an effective method for managing rodent populations.

Correction to: Protecting pollinators and our food supply: understanding and managing threats to pollinator health - H. Siviter; A. Fisher; B. Baer; M. J. F. Brown; I. F. Camargo; J. Cole; Y. Le Conte; B. Dorin; J. D. Evans; W. Farina; J. Fine; L. R. Fischer; et al. (Insectes Sociaux, 2023)

Interaction of physico-chemical parameters with Shannon-Weaver Diversity Index based on phytoplankton diversity in coastal water of Diu, India - Atanu Kumar Panja; Sonpal Vasavdutta; Meena Choudhary; Indirapriyatharsini Thiyagarajan; Ambika H. Shinde; Sanak Ray; Tarini P. Sahoo; Shruti Chatterjee; Ravikumar B. Thorat; Anil Kumar Madhava; Soumya Haldar (Marine Pollution Bulletin, 2023)

Tracing hydrothermal mineral thenardite in geysers/hot springs of North-western Himalayan belt, Ladakh Geothermal Province, India by hydrogeochemistry, fluid-mineral equilibria and isotopic studies - Archisman Dutta; Parashar Mishra; Ahsan Absar; Vivek P. Malviya; P.K. Singh; Ajay Srivastava; Biswajit Ray; Alok Kumar; N.V. Nitnaware (Geochemistry, 2023)

Microbathymetry inferences from two AUV dives over a short segment of the Central Indian Ridge between 10°18′ and 10°57′S, Indian Ocean - K. A. Kamesh Raju; V. Yatheesh; A. Srinivas Rao; L. Surya Prakash; Durbar Ray; Abhay Mudholkar; Kiranmai Samudrala; Nico Augustin; P. John Kurian (Geo-Marine Letters, 2023)

Protecting pollinators and our food supply: understanding and managing threats to pollinator health - H. Siviter; A. Fisher; B. Baer; M. J. F. Brown; I. F. Camargo; J. Cole; Y. Le Conte; B. Dorin; J. D. Evans; W. Farina; J. Fine; L. R. Fischer; et al. (Insectes Sociaux, 2023)
Global pollinator declines threaten food production and natural ecosystems. The drivers of declines are complicated and driven by numerous factors such as pesticide use, loss of habitat, rising pathogens due to commercial bee keeping and climate change. Halting and reversing pollinator declines will require a multidisciplinary approach and international cooperation. Here, we summarize 20 presentations given in the symposium ‘Protecting pollinators and our food supply: Understanding and managing threats to pollinator health’ at the 19th Congress of the International Union for the Study of Social Insects in San Diego, 2022. We then synthesize the key findings and discuss future research areas such as better understanding the impact of anthropogenic stressors on wild bees.

A magnetically separable α-NiMoO4/ZnFe2O4/coffee biochar heterojunction photocatalyst for efficient ketoprofen degradation - Schindra Kumar Ray; P Anil Kumar Reddy; Sunho Yoon; Jaegwan Shin; Kangmin Chon; Sungjun Bae (Chemical Engineering Journal, 2023)

Marine bioactive compounds as antibiofilm agent: a metabolomic approach - Dibyajit Lahiri; Moupriya Nag; Ankita Dey; Tanmay Sarkar; Siddhartha Pati; Nilesh P. Nirmal; Rina Rani Ray; Vijay Jagdish Upadhye; Soumya Pandit; M. Moovendhan; M. Kavisri (Archives of Microbiology, 2023)

Sustainable Growing Areas for Sugarcane in Sri Lanka Under a Changing Climate - D. M. B. M. Deegala; N. S. Abeysingha; L. P. Muthuwatta; Ram L. Ray (Sugar Tech, 2022)

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

A history and evaluation of catch‐only stock assessment models - Daniel Ovando; Christopher M. Free; Olaf P. Jensen; Ray Hilborn (Fish and Fisheries, 2022)
Understanding the status of fish stocks is a critical step in ensuring the ecological and economic sustainability of marine ecosystems. However, at least half of global catch and a vast majority of global fisheries lack formal stock assessments, largely due to a lack of sufficient data. Catch data, loosely referring to any catch records be it inclusive of discards or not, are the only type of fishery data available across a wide range of fisheries at a global scale. This has given rise to a long list of so‐called “catch‐only” models, intended to estimate aspects of stock status based primarily on characteristics of a fishery's catch history. In this paper, we review the history, performance and potential of “catch‐only” models to estimate stock biomass status. While individual catch‐only models often report good performance, repeated efforts to examine the performance of these models have consistently found them to be imprecise and biased when applied to new data‐limited fisheries. We demonstrate that a large reason for this is the simple lack of information on stock status contained in the shape of a catch history alone. Off‐the‐shelf use of catch‐only models can lead to poor and biased estimates of stock status, potentially hindering efforts at effective management.

Disorders of Tetrahydrobiopterin Metabolism: Experience from South India - Somdattaa Ray; Hansashree Padmanabha; Vykuntaraju K. Gowda; Rohan Mahale; Rita Christopher; Shruthy Sreedharan; Debjyoti Dhar; Mahesh Kamate; Madhu Nagappa; Maya Bhat; Rammurthy Anjanappa; Gautham Arunachal; et al. (Metabolic Brain Disease, 2022)

Valorization of waste potato peel as iron adsorbent and catalyst in photo-oxidation: a sustainable waste management strategy - P. Dey; R. Koijam; S. Ray (International Journal of Environmental Science and Technology, 2022)

Applications of Advanced Geospatial Technology for Expansion of Area under Horticultural Crops in North Eastern Region of India - B. K. Handique; C. Goswami; P. Jena; F. Dutta; R. Samiam; I. Nongrum; D. Jha; P. L. N. Raju; C. R. Deka; R. Sarma; K. Sarmah; H. K. Dutta; et al. (Journal of the Indian Society of Remote Sensing, 2022)

Assimilation of Remote Sensing Data into Crop Growth Model for Yield Estimation: A Case Study from India - Murali Krishna Gumma; M. D. M. Kadiyala; Pranay Panjala; Shibendu S. Ray; Venkata Radha Akuraju; Sunil Dubey; Andrew P. Smith; Rajesh Das; Anthony M. Whitbread (Journal of the Indian Society of Remote Sensing, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

An Overview on Promising Somatic Cell Sources Utilized for the Efficient Generation of Induced Pluripotent Stem Cells - Arnab Ray; Jahnavy Madhukar Joshi; Pradeep Kumar Sundaravadivelu; Khyati Raina; Nibedita Lenka; Vishwas Kaveeshwar; Rajkumar P Thummer (Stem Cell Reviews and Reports, 2021)

Large‐scale genome sampling reveals unique immunity and metabolic adaptations in bats - Diana D. Moreno Santillán; Tanya M. Lama; Yocelyn T. Gutierrez Guerrero; Alexis M. Brown; Paul Donat; Huabin Zhao; Stephen J. Rossiter; Laurel R. Yohe; Joshua H. Potter; Emma C. Teeling; Sonja C. Vernes; Kalina T. J. Davies; et al. (Molecular Ecology, 2021)
Comprising more than 1,400 species, bats possess adaptations unique among mammals including powered flight, unexpected longevity, and extraordinary immunity. Some of the molecular mechanisms underlying these unique adaptations includes DNA repair, metabolism and immunity. However, analyses have been limited to a few divergent lineages, reducing the scope of inferences on gene family evolution across the Order Chiroptera. We conducted an exhaustive comparative genomic study of 37 bat species, one generated in this study, encompassing a large number of lineages, with a particular emphasis on multi‐gene family evolution across immune and metabolic genes. In agreement with previous analyses, we found lineage‐specific expansions of the APOBEC3 and MHC‐I gene families, and loss of the proinflammatory PYHIN gene family. We inferred more than 1,000 gene losses unique to bats, including genes involved in the regulation of inflammasome pathways such as epithelial defence receptors, the natural killer gene complex and the interferon‐gamma induced pathway. Gene set enrichment analyses revealed genes lost in bats are involved in defence response against pathogen‐associated molecular patterns and damage‐associated molecular patterns. Gene family evolution and selection analyses indicate bats have evolved fundamental functional differences compared to other mammals in both innate and adaptive immune system, with the potential to enhance antiviral immune response while dampening inflammatory signalling. In addition, metabolic genes have experienced repeated expansions related to convergent shifts to plant‐based diets. Our analyses support the hypothesis that, in tandem with flight, ancestral bats had evolved a unique set of immune adaptations whose functional implications remain to be explored.

Evaluating impacts of forage fish abundance on marine predators - Christopher M. Free; Olaf P. Jensen; Ray Hilborn (Conservation Biology, 2021)
Forage fish—small, low trophic level, pelagic fish such as herrings, sardines, and anchovies—are important prey species in marine ecosystems and also support large commercial fisheries. In many parts of the world, forage fish fisheries are managed using precautionary principles that target catch limits below the maximum sustainable yield. However, there are increasing calls to further limit forage fish catch to safeguard their fish, seabird, and marine mammal predators. The effectiveness of these extra‐precautionary regulations, which assume that increasing prey abundance increases predator productivity, are under debate. In this study, we used prey‐linked population models to measure the influence of forage fish abundance on the population growth rates of 45 marine predator populations representing 32 fish, seabird, and mammal species from 5 regions around the world. We used simulated data to confirm the ability of the statistical model to accurately detect prey influences under varying levels of influence strength and process variability. Our results indicate that predator productivity was rarely influenced by the abundance of their forage fish prey. Only 6 predator populations (13% of the total) were positively influenced by increasing prey abundance and the model exhibited high power to detect prey influences when they existed. These results suggest that additional limitation of forage fish harvest to levels well below sustainable yields would rarely result in detectable increases in marine predator populations.

Removal of textile dyes from water by jute stick activated carbon: process optimization and isotherm studies - R. K. Ghosh; D. P. Ray; A. Tewari; I. Das (International Journal of Environmental Science and Technology, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Assessment of groundwater depletion–induced land subsidence and characterisation of damaging cracks on houses: a case study in Mohali-Chandigarh area, India - Neha Kadiyan; R. S. Chatterjee; Pranshu Pranjal; Pankaj Agrawal; S. K. Jain; M. L. Angurala; A. K. Biyani; M. S. Sati; Dheeraj Kumar; Ashutosh Bhardwaj; P. K. Champati Ray (Bulletin of Engineering Geology and the Environment, 2021)

Estimating unconfined compressive behavior of HMA using soft computing - Lee P. Leon; Indrajit Ray (Innovative Infrastructure Solutions, 2021)

β-Adrenoceptor blockade prevents carotid body hyperactivity and elevated vascular sympathetic nerve density induced by chronic intermittent hypoxia - Abdulaziz A. Alzahrani; Lily L. Cao; Hayyaf S. Aldossary; Demitris Nathanael; Jiarong Fu; Clare J. Ray; Keith L. Brain; Prem Kumar; Andrew M. Coney; Andrew P. Holmes (Pflügers Archiv - European Journal of Physiology, 2021)
Carotid body (CB) hyperactivity promotes hypertension in response to chronic intermittent hypoxia (CIH). The plasma concentration of adrenaline is reported to be elevated in CIH and our previous work suggests that adrenaline directly activates the CB. However, a role for chronic adrenergic stimulation in mediating CB hyperactivity is currently unknown. This study evaluated whether beta-blocker treatment with propranolol (Prop) prevented the development of CB hyperactivity, vascular sympathetic nerve growth and hypertension caused by CIH. Adult male Wistar rats were assigned into 1 of 4 groups: Control (N), N + Prop, CIH and CIH + Prop. The CIH paradigm consisted of 8 cycles h −1 , 8 h day −1 , for 3 weeks. Propranolol was administered via drinking water to achieve a dose of 40 mg kg −1 day −1 . Immunohistochemistry revealed the presence of both β 1 and β 2 -adrenoceptor subtypes on the CB type I cell. CIH caused a 2–3-fold elevation in basal CB single-fibre chemoafferent activity and this was prevented by chronic propranolol treatment. Chemoafferent responses to hypoxia and mitochondrial inhibitors were attenuated by propranolol, an effect that was greater in CIH animals. Propranolol decreased respiratory frequency in normoxia and hypoxia in N and CIH. Propranolol also abolished the CIH mediated increase in vascular sympathetic nerve density. Arterial blood pressure was reduced in propranolol groups during hypoxia. Propranolol exaggerated the fall in blood pressure in most (6/7) CIH animals during hypoxia, suggestive of reduced sympathetic tone. These findings therefore identify new roles for β-adrenergic stimulation in evoking CB hyperactivity, sympathetic vascular hyperinnervation and altered blood pressure control in response to CIH.

Contribution of IRS-1C Data to Agricultural Monitoring: A Review - Shibendu S. Ray; Raghavendra P. Singh; Karan Choudhary (Journal of the Indian Society of Remote Sensing, 2021)

Trawl fishing impacts on the status of seabed fauna in diverse regions of the globe - Tessa Mazor; C. Roland Pitcher; Wayne Rochester; Michel J. Kaiser; Jan G. Hiddink; Simon Jennings; Ricardo Amoroso; Robert A. McConnaughey; Adriaan D. Rijnsdorp; Ana M. Parma; Petri Suuronen; Jeremy Collie; et al. (Fish and Fisheries, 2021)
Bottom trawl fishing is a controversial activity. It yields about a quarter of the world's wild seafood, but also has impacts on the marine environment. Recent advances have quantified and improved understanding of large‐scale impacts of trawling on the seabed. However, such information needs to be coupled with distributions of benthic invertebrates (benthos) to assess whether these populations are being sustained under current trawling regimes. This study collated data from 13 diverse regions of the globe spanning four continents. Within each region, we combined trawl intensity distributions and predicted abundance distributions of benthos groups with impact and recovery parameters for taxonomic classes in a risk assessment model to estimate benthos status. The exposure of 220 predicted benthos‐group distributions to trawling intensity (as swept area ratio) ranged between 0% and 210% (mean = 37%) of abundance. However, benthos status, an indicator of the depleted abundance under chronic trawling pressure as a proportion of untrawled state, ranged between 0.86 and 1 (mean = 0.99), with 78% of benthos groups > 0.95. Mean benthos status was lowest in regions of Europe and Africa, and for taxonomic classes Bivalvia and Gastropoda. Our results demonstrate that while spatial overlap studies can help infer general patterns of potential risk, actual risks cannot be evaluated without using an assessment model that incorporates trawl impact and recovery metrics. These quantitative outputs are essential for sustainability assessments, and together with reference points and thresholds, can help managers ensure use of the marine environment is sustainable under the ecosystem approach to management.

Attempted Isolation of Cryptococcus Species and Incidental Isolation of Exophiala dermatitidis from Human Oral Cavities - Caroline P. Toberna; Jessica J. F. Kram; Eric T. Beck; Sommer Ray; Tyler Gavinski; Alana K. Sterkel; Dennis J. Baumgardner (Mycopathologia, 2020)

Stable quantitative trait locus (QTL) for sheath blight resistance from rice cultivar CR 1014 - Archana Bal; Pankajini Samal; Mridul Chakraborti; Arup Kumar Mukherjee; Soham Ray; Kutubuddin A. Molla; Lambodar Behera; Rashmita Samal; Sarmistha Sarangi; Pritiranjan Sahoo; Motilal Behera; Srikanta Lenka; et al. (Euphytica, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

John Leonard Bannister 1937–2018 - Robert L. Brownell; Doug S. Butterworth; Catherine M. Kemper; Martin Cawthorn; Michael Double; Greg P. Donovan; Ray Gambell; Hidehiro Kato (Marine Mammal Science, 2020)

Identification and genotypic characterization of porcine teschovirus from selected pig populations in India - Pradeep K. Ray; P. A. Desingu; R. Anoopraj; R. K Singh; G. Saikumar (Tropical Animal Health and Production, 2020)

Thunderstorm dynamics through wind profiling features: the first observation by stratospheric-tropospheric radar of GU - M. Devi; S. Patgiri; A. Medhi; S. Das; M. Saikia; A. K. Barbara; S. S. Kakatkar; K. P. Ray (Natural Hazards, 2020)

Correction to: Documenting lemming population change in the Arctic: Can we detect trends? - Dorothée Ehrich; Niels M. Schmidt; Gilles Gauthier; Ray Alisauskas; Anders Angerbjörn; Karin Clark; Frauke Ecke; Nina E. Eide; Erik Framstad; Jay Frandsen; Alastair Franke; Olivier Gilg; et al. (Ambio, 2020)

Documenting lemming population change in the Arctic: Can we detect trends? - Dorothée Ehrich; Niels M. Schmidt; Gilles Gauthier; Ray Alisauskas; Anders Angerbjörn; Karin Clark; Frauke Ecke; Nina E. Eide; Erik Framstad; Jay Frandsen; Alastair Franke; Olivier Gilg; et al. (Ambio, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Diversity of hepatitis C virus infection among HIV-infected people who inject drugs in India - S. S. Solomon; D. Boon; S. Saravanan; A. K. Srikrishnan; C. K. Vasudevan; P. Balakrishnan; D. Persaud; S. C. Ray; S. Mehta; S. H. Mehta (VirusDisease, 2019)

Enhanced Production of Shigella flexneri Polysaccharide from a Newly Devised Silicate Method as a Potential Vaccine Conjugate - P. V. S. L. S. S. Narayana; Jayati Ray Dutta (Current Microbiology, 2019)

Pastoral yak rearing system is changing with change in climate: an exploration of North Sikkimin Eastern Himalaya - Sheikh Mohammad Feroze; Lala I. P. Ray; Koijam Johny Singh; Ram Singh (Climatic Change, 2019)

Prolonged exposure to manure from livestock‐administered antibiotics decreases ecosystem carbon‐use efficiency and alters nitrogen cycling - Carl Wepking; Brian Badgley; John E. Barrett; Katharine F. Knowlton; Jane M. Lucas; Kevan J. Minick; Partha P. Ray; Sarah E. Shawver; Michael S. Strickland (Ecology Letters, 2019)
Microbial communities drive soil ecosystem function but are also susceptible to environmental disturbances. We investigated whether exposure to manure sourced from cattle either administered or not administered antibiotics affected microbially mediated terrestrial ecosystem function. We quantified changes in microbial community composition via amplicon sequencing, and terrestrial elemental cycling via a stable isotope pulse‐chase. Exposure to manure from antibiotic‐treated cattle caused: (i) changes in microbial community structure; and (ii) alterations in elemental cycling throughout the terrestrial system. This exposure caused changes in fungal : bacterial ratios, as well as changes in bacterial community structure. Additionally, exposure to manure from cattle treated with pirlimycin resulted in an approximate two‐fold increase in ecosystem respiration of recently fixed‐carbon, and a greater proportion of recently added nitrogen in plant and soil pools compared to the control manure. Manure from antibiotic‐treated cattle therefore affects terrestrial ecosystem function via the soil microbiome, causing decreased ecosystem carbon use efficiency, and altered nitrogen cycling.

Renewable energy and sustainability - P. Ray (Clean Technologies and Environmental Policy, 2019)

Towards Comprehensive Observing and Modeling Systems for Monitoring and Predicting Regional to Coastal Sea Level - Rui M. Ponte; Mark Carson; Mauro Cirano; Catia M. Domingues; Svetlana Jevrejeva; Marta Marcos; Gary Mitchum; R. S. W. van de Wal; Philip L. Woodworth; Michaël Ablain; Fabrice Ardhuin; Valérie Ballu; et al. (Frontiers in Marine Science, 2019)

Integration of satellite remote sensing and geophysical techniques (electrical resistivity tomography and ground penetrating radar) for landslide characterization at Kunjethi (Kalimath), Garhwal Himalaya, India - Suresh Kannaujiya; Shovan Lal Chattoraj; Dilhani Jayalath; Prashant Kumar Champati ray; Kushank Bajaj; Shilpika Podali; M. P. S. Bisht (Natural Hazards, 2019)

Novel biotic stress responsive candidate gene based SSR (cgSSR) markers from rice - Kutubuddin Ali Molla; T. P. Muhammed Azharudheen; Soham Ray; Sutapa Sarkar; Alaka Swain; Mridul Chakraborti; Joshitha Vijayan; Onkar Nath Singh; Mirza Jaynul Baig; Arup Kumar Mukherjee (Euphytica, 2019)

Stability of expression of Cry1Ac and Cry2Ab2 proteins in Bollgard-II hybrids at different stages of crop growth in different genotypes across cropping seasons and multiple geographies - Anik Luke Dhanaraj; Alan Ray Willse; S. P. Kamath (Transgenic Research, 2019)

Beneficial effects of fenofibrate in pulmonary hypertension in rats - Palak Galhotra; Pankaj Prabhakar; Himanshu Meghwani; Soheb A. Mohammed; Sanjay Kumar Banerjee; Sandeep Seth; Milind P. Hote; K. H. Reeta; Ruma Ray; Subir Kumar Maulik (Molecular and Cellular Biochemistry, 2018)

A review of regulations and guidelines related to winter manure application - Jian Liu; Peter J. A. Kleinman; Helena Aronsson; Don Flaten; Richard W. McDowell; Marianne Bechmann; Douglas B. Beegle; Timothy P. Robinson; Ray B. Bryant; Hongbin Liu; Andrew N. Sharpley; Tamie L. Veith (Ambio, 2018)

Priority Zoning of Available Micronutrients in the Soils of Agro-ecological Sub-regions of North-East India Using Geo-spatial Techniques - Siladitya Bandyopadhyay; Prasenjit Ray; Shelton Padua; S. Ramachandran; Roomesh Kumar Jena; Partha Deb Roy; D. P. Dutta; Surendra Kumar Singh; Sanjay Kumar Ray (Agricultural Research, 2018)

Ecology of Endomycorrhizal Association in Musa spp. of South India - K. S. Nidheesh; N. Valsalakumar; V. P. Potty; J. G. Ray (Symbiosis, 2018)

Vitamin D3 attenuates cognitive deficits and neuroinflammatory responses in ICV-STZ induced sporadic Alzheimer’s disease - P. Yamini; R. S. Ray; Kanwaljit Chopra (Inflammopharmacology, 2018)

Re-evaluating conservation priorities of New World tarantulas (Araneae: Theraphosidae) in a molecular framework indicates non-monophyly of the genera, Aphonopelma and Brachypelma - Steven P. Turner; Stuart J. Longhorn; Chris A. Hamilton; Ray Gabriel; Fernando PÉrez-Miles; Alfried P. Vogler (Systematics and Biodiversity, 2018)

Earthquake induced liquefaction hazard, probability and risk assessment in the city of Kolkata, India: its historical perspective and deterministic scenario - Sankar Kumar Nath; Nishtha Srivastava; Chitralekha Ghatak; Manik Das Adhikari; Ambarish Ghosh; S. P. Sinha Ray (Journal of Seismology, 2018)

Effect of Rainfall Variability on Rice Yield in North Eastern Hills of India: A Case Study - Deotrephy K. Dkhar; S. M. Feroze; Ram Singh; Lala I. P. Ray (Agricultural Research, 2017)

Evaluating species-specific changes in hydrologic regimes: an iterative approach for salmonids in the Greater Yellowstone Area (USA) - Robert Al-Chokhachy; Adam J. Sepulveda; Andrew M. Ray; David P. Thoma; Michael T. Tercek (Reviews in Fish Biology and Fisheries, 2017)

Transcriptomic effects of adenosine 2A receptor deletion in healthy and endotoxemic murine myocardium - Kevin J. Ashton; Melissa E. Reichelt; S. Jamal Mustafa; Bunyen Teng; Catherine Ledent; Lea M. D. Delbridge; Polly A. Hofmann; R. Ray Morrison; John P. Headrick (Purinergic Signalling, 2017)

Nano silver-embedded electrospun nanofiber of poly(4-chloro-3-methylphenyl methacrylate): use as water sanitizer - Mehdihasan I. Shekh; Nirmal N. Patel; Kaushal P. Patel; Rajnikant M. Patel; Arabinda Ray (Environmental Science and Pollution Research, 2017)

Effects of biological, economic and management factors on tuna and billfish stock status - Maite Pons; Trevor A Branch; Michael C Melnychuk; Olaf P Jensen; Jon Brodziak; Jean M Fromentin; Shelton J Harley; Alan C Haynie; Laurie T Kell; Mark N Maunder; Ana M Parma; Victor R Restrepo; et al. (Fish and Fisheries, 2017)
Commercial tunas and billfishes (swordfish, marlins and sailfish) provide considerable catches and income in both developed and developing countries. These stocks vary in status from lightly exploited to rebuilding to severely depleted. Previous studies suggested that this variability could result from differences in life‐history characteristics and economic incentives, but differences in exploitation histories and management measures also have a strong effect on current stock status. Although the status (biomass and fishing mortality rate) of major tuna and billfish stocks is well documented, the effect of these diverse factors on current stock status and the effect of management measures in rebuilding stocks have not been analysed at the global level. Here, we show that, particularly for tunas, stocks were more depleted if they had high commercial value, were long‐lived species, had small pre‐fishing biomass and were subject to intense fishing pressure for a long time. In addition, implementing and enforcing total allowable catches ( TAC s) had the strongest positive influence on rebuilding overfished tuna and billfish stocks. Other control rules such as minimum size regulations or seasonal closures were also important in reducing fishing pressure, but stocks under TAC implementations showed the fastest increase of biomass. Lessons learned from this study can be applied in managing large industrial fisheries around the world. In particular, tuna regional fisheries management organizations should consider the relative effectiveness of management measures observed in this study for rebuilding depleted large pelagic stocks.

Mineral chemistry of tourmaline from Mashak Pahar, South Purulia Shear Zone (SPSZ), eastern Indian Shield - SANTANU ACHARJEE; JYOTISANKAR RAY; PAYEL DEY; DEBAPRIYA BHATTACHARYYA; MOUSUMI BANERJEE; BASAB CHATTOPADHYAY; SHYAMAL SENGUPTA; A K BHATT; D CHOWDHURY; A K DWIVEDI; SANJOY MAHATO; ARKA RANJAN JANA; et al. (Journal of Earth System Science, 2016)

Predictive equations for soil shear-wave velocities of Hungarian soils based on MASW and CPT measurements around Győr - O. Kegyes-Brassai; R. P. Ray; P. Tildy (Acta Geodaetica et Geophysica, 2016)

Dynamic N ‐occupancy models: estimating demographic rates and local abundance from detection‐nondetection data - Sam Rossman; Charles B. Yackulic; Sarah P. Saunders; Janice Reid; Ray Davis; Elise F. Zipkin (Ecology, 2016)
Occupancy modeling is a widely used analytical technique for assessing species distributions and range dynamics. However, occupancy analyses frequently ignore variation in abundance of occupied sites, even though site abundances affect many of the parameters being estimated (e.g., extinction, colonization, detection probability). We introduce a new model (“dynamic N ‐occupancy”) capable of providing accurate estimates of local abundance, population gains (reproduction/immigration), and apparent survival probabilities while accounting for imperfect detection using only detection/nondetection data. Our model utilizes heterogeneity in detection based on variations in site abundances to estimate latent demographic rates via a dynamic N ‐mixture modeling framework. We validate our model using simulations across a wide range of values and examine the data requirements, including the number of years and survey sites needed, for unbiased and precise estimation of parameters. We apply our model to estimate spatiotemporal heterogeneity in abundances of barred owls ( Strix varia ) within a recently invaded region in Oregon (USA). Estimates of apparent survival and population gains are consistent with those from a nearby radio‐tracking study and elucidate how barred owl abundances have increased dramatically over time. The dynamic N ‐occupancy model greatly improves inferences on individual‐level population processes from occupancy data by explicitly modeling the latent population structure.

Feasibility of Singlet Analysis for Ligand Binding Assays: a Retrospective Examination of Data Generated Using the Gyrolab Platform - Tracey H. Clark; Phillip D. Yates; Allison Given Chunyk; Alison P. Joyce; Aidong Wu; Petar Pop-Damkov; Yiqun Zhang; Elizabeth A. Dreher; Laurie A. Tylaska; Jo-Ann A. Wentland; Kathleen B. Pelletier; Lindsay E. King; et al. (The AAPS Journal, 2016)

Prioritization of knowledge‐needs to achieve best practices for bottom trawling in relation to seabed habitats - Michel J Kaiser; Ray Hilborn; Simon Jennings; Ricky Amaroso; Michael Andersen; Kris Balliet; Eric Barratt; Odd A Bergstad; Stephen Bishop; Jodi L Bostrom; Catherine Boyd; Eduardo A Bruce; et al. (Fish and Fisheries, 2016)
Management and technical approaches that achieve a sustainable level of fish production while at the same time minimizing or limiting the wider ecological effects caused through fishing gear contact with the seabed might be considered to be ‘best practice’. To identify future knowledge‐needs that would help to support a transition towards the adoption of best practices for trawling, a prioritization exercise was undertaken with a group of 39 practitioners from the seafood industry and management, and 13 research scientists who have an active research interest in bottom‐trawl and dredge fisheries. A list of 108 knowledge‐needs related to trawl and dredge fisheries was developed in conjunction with an ‘expert task force’. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge‐need. The top 25 knowledge‐needs are presented, as scored separately by practitioners and scientists. There was considerable consistency in the priorities identified by these two groups. The top priority knowledge‐need to improve current understanding on the distribution and extent of different habitat types also reinforced the concomitant need for the provision and access to data on the spatial and temporal distribution of all forms of towed bottom‐fishing activities. Many of the other top 25 knowledge‐needs concerned the evaluation of different management approaches or implementation of different fishing practices, particularly those that explore trade‐offs between effects of bottom trawling on biodiversity and ecosystem services and the benefits of fish production as food.

Soybean Aphid Response to their Alarm Pheromone E-ß-Farnesene (EBF) - Jaclyn L. Eichele; Jamin Dreyer; Ray Heinz; Stephen P. Foster; Deirdre A. Prischmann-Voldseth; Jason P. Harmon (Journal of Insect Behavior, 2016)

Radioelemental, petrological and geochemical characterization of the Bundelkhand craton, central India: implication in the Archaean geodynamic evolution - Labani Ray; P. Nagaraju; S. P. Singh; G. Ravi; Sukanta Roy (International Journal of Earth Sciences, 2016)

Kedarnath disaster 2013: causes and consequences using remote sensing inputs - P. K. Champati Ray; Shovan Lal Chattoraj; M. P. S. Bisht; Suresh Kannaujiya; Kamal Pandey; Ajanta Goswami (Natural Hazards, 2016)

More is not necessarily better: the interaction between insect population density and culture age of fungus on the control of invasive weed water hyacinth - Puja Ray; Martin P. Hill (Hydrobiologia, 2016)

Comparison of low-carbon pathways for California - Geoffrey M. Morrison; Sonia Yeh; Anthony R. Eggert; Christopher Yang; James H. Nelson; Jeffery B. Greenblatt; Raphael Isaac; Mark Z. Jacobson; Josiah Johnston; Daniel M. Kammen; Ana Mileva; Jack Moore; et al. (Climatic Change, 2015)

Life at the leading edge: genetic impoverishment of the spotted bass, Micropterus punctulatus, at its Western edge - J. W. Ray; M. Husemann; D. J. Lutz-Carrillo; R. S. King; P. D. Danley (Environmental Biology of Fishes, 2015)

Spatial prediction of landslide susceptibility in parts of Garhwal Himalaya, India, using the weight of evidence modelling - Pardeep Kumar Guri; P. K. Champati ray; Ramesh Chandra Patel (Environmental Monitoring and Assessment, 2015)

Methane and nitrous oxide emissions from rice and maize production in diversified rice cropping systems - Sebastian Weller; David Kraus; Kevin Ray P. Ayag; Reiner Wassmann; M. C. R. Alberto; Klaus Butterbach-Bahl; Ralf Kiese (Nutrient Cycling in Agroecosystems, 2015)

The energy‐conserving electron transfer system used by D esulfovibrio alaskensis strain G 20 during pyruvate fermentation involves reduction of endogenously formed fumarate and cytoplasmic and membrane‐bound complexes, Hdr‐Flox and Rnf - Birte Meyer; Jennifer V. Kuehl; Morgan N. Price; Jayashree Ray; Adam M. Deutschbauer; Adam P. Arkin; David A. Stahl (Environmental Microbiology, 2014)
Summary The adaptation capability of D esulfovibrio to natural fluctuations in electron acceptor availability was evaluated by studying D esulfovibrio alaskensis strain G 20 under varying respiratory, fermentative and methanogenic coculture conditions in chemostats. Transition from lactate to pyruvate in coculture resulted in a dramatic shift in the population structure and closer interspecies cell‐to‐cell interactions. Lower methane production rates in coculture than predicted from pyruvate input was attributed to redirection of electron flow to fumarate reduction. Without a methanogenic partner, accumulation of H 2 and formate resulted in greater succinate production. Comparative transcript and gene fitness analysis in concert with physiological data of G 20 wildtype and mutants demonstrated that pyruvate fermentation involves respiration of cytoplasmically formed fumarate using cytoplasmic and membrane‐bound energy‐conserving complexes, Rnf , Hdr‐Flox ‐1 and Hmc. At the low H 2 /formate levels maintained in coculture, Rnf likely functions as proton‐pumping ferredoxin (Fd) : type‐I cytochrome c oxidoreductase, which transitions to a proton‐pumping Fd red : nicotinamide adenine dinucleotide ( NAD + ) oxidoreductase at high H 2 /formate levels during fermentation in monoculture. Hdr‐Flox ‐1 is postulated to recycle Fd red via a flavin‐based electron bifurcation involving NADH , Fd ox and the thiol/disulphide‐containing DsrC . In a menaquinone ( MQ )‐based electron confurcation reaction, the high‐molecular‐weight cytochrome‐c 3 complex, Hmc , is proposed to then couple DsrC red and periplasmic H 2 /formate oxidation using the MQ pool to fuel a membrane‐bound fumarate reductase.

Can intense predation by bears exert a depensatory effect on recruitment in a Pacific salmon population? - Thomas P. Quinn; Curry J. Cunningham; Jessica Randall; Ray Hilborn (Oecologia, 2014)

Microbial Biomass Carbon Status in Agro-Ecological Sub Regions of Black Soils in India - Kulandaivelu Velmourougane; M. V. Venugopalan; T. Bhattacharyya; Dipak Sarkar; D. K. Pal; Apeksha Sahu; P. Chandran; S. K. Ray; Champa Mandal; K. M. Nair; Jagdish Prasad; R. S. Singh; et al. (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2014)

Trends in seasonal temperatures over the Indian region - Nilesh K Wagholikar; K C Sinha Ray; P N Sen; P Pradeep Kumar (Journal of Earth System Science, 2014)

Developing Spectral Library of Major Plant Species of Western Himalayas Using Ground Observations - K. R. Manjunath; Amit Kumar; Mehra Meenakshi; R. Renu; S. K. Uniyal; R. D. Singh; P. S. Ahuja; S. S. Ray; Sushma Panigrahy (Journal of the Indian Society of Remote Sensing, 2014)

Urease Activity in Various Agro-ecological Sub-regions of Black Soil Regions of India - Kulandaivelu Velmourougane; M. V. Venugopalan; T. Bhattacharyya; Dipak Sarkar; D. K. Pal; Apeksha Sahu; P. Chandran; S. K. Ray; Champa Mandal; K. M. Nair; Jagdish Prasad; R. S. Singh; et al. (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2013)

Targeting oncogenic ALK and MET: a promising therapeutic strategy for glioblastoma - Gerald C. Wallace; Yaenette N. Dixon-Mah; W. Alex Vandergrift; Swapan K. Ray; Catherine P. Haar; Amber M. Mittendorf; Sunil J. Patel; Naren L. Banik; Pierre Giglio; Arabinda Das (Metabolic Brain Disease, 2013)

Morphometric Correlation of Impulsivity in Medial Prefrontal Cortex - Sang Soo Cho; Giovanna Pellecchia; Kelly Aminian; Nicola Ray; Barbara Segura; Ignacio Obeso; Antonio P. Strafella (Brain Topography, 2013)

SCS-CN Based Quantification of Potential of Rooftop Catchments and Computation of ASRC for Rainwater Harvesting - P. K. Singh; B. K. Yaduvanshi; Swati Patel; Saswati Ray (Water Resources Management, 2013)

Agricultural Area Diversification and Crop Water Demand Analysis: A Remote Sensing and GIS Approach - B. U. Choudhury; Anil Sood; S. S. Ray; P. K. Sharma; S. Panigrahy (Journal of the Indian Society of Remote Sensing, 2013)

Acaricide resistance status in Indian isolates of Hyalomma anatolicum - K. P. Shyma; Sachin Kumar; Anil Kumar Sharma; D. D. Ray; S. Ghosh (Experimental and Applied Acarology, 2012)

IGS08: the IGS realization of ITRF2008 - P. Rebischung; J. Griffiths; J. Ray; R. Schmid; X. Collilieux; B. Garayt (GPS Solutions, 2012)

Connectivity of prairie dog colonies in an altered landscape: inferences from analysis of microsatellite DNA variation - Loren C. Sackett; Todd B. Cross; Ryan T. Jones; Whitney C. Johnson; Kimberly Ballare; Chris Ray; Sharon K. Collinge; Andrew P. Martin (Conservation Genetics, 2012)

Defining Trade‐Offs among Conservation, Profitability, and Food Security in the California Current Bottom‐Trawl Fishery - RAY HILBORN; IAN J. STEWART; TREVOR A. BRANCH; OLAF P. JENSEN (Conservation Biology, 2012)
Although it is recognized that marine wild‐capture fisheries are an important source of food for much of the world, the cost of sustainable capture fisheries to species diversity is uncertain, and it is often questioned whether industrial fisheries can be managed sustainably. We evaluated the trade‐off among sustainable food production, profitability, and conservation objectives in the groundfish bottom‐trawl fishery off the U.S. West Coast, where depletion (i.e., reduction in abundance) of six rockfish species (Sebastes) is of particular concern. Trade‐offs are inherent in this multispecies fishery because there is limited capacity to target species individually. From population models and catch of 34 stocks of bottom fish, we calculated the relation between harvest rate, long‐term yield (i.e., total weight of fish caught), profit, and depletion of each species. In our models, annual ecosystem‐wide yield from all 34 stocks was maximized with an overall 5.4% harvest rate, but profit was maximized at a 2.8% harvest rate. When we reduced harvest rates to the level (2.2% harvest rate) at which no stocks collapsed ( 30% of total sustainable yield, whereas yield lost from stock depletion was 3% of total sustainable yield. There are clear conservation benefits to lower harvest rates, but avoiding overfishing of all stocks in a multispecies fishery carries a substantial cost in terms of lost yield and profit.

Ligand Binding Assays in the 21st Century Laboratory: Platforms - Franklin P. Spriggs; Zhandong Don Zhong; Afshin Safavi; Darshana Jani; Narasaiah Dontha; Anita Kant; Jenny Ly; Lia Brilando; Karolina Österlund; Nathalie Rouleau; Saloumeh Kadkhodayan Fischer; Martin Boissonneault; et al. (The AAPS Journal, 2012)

Marine fisheries as ecological experiments - Olaf P. Jensen; Trevor A. Branch; Ray Hilborn (Theoretical Ecology, 2012)

(R)-Desmolactone, A Female-produced Sex Pheromone Component of the Cerambycid Beetle Desmocerus californicus californicus (subfamily Lepturinae) - Ann M. Ray; Ian P. Swift; J. Steven McElfresh; Ronald L. Alten; Jocelyn G. Millar (Journal of Chemical Ecology, 2012)

Regional landslide susceptibility: spatiotemporal variations under dynamic soil moisture conditions - Ram L. Ray; Jennifer M. Jacobs; Thomas P. Ballestero (Natural Hazards, 2011)

Comparison of Two Data Smoothing Techniques for Vegetation Spectra Derived From EO-1 Hyperion - Anshu Miglani; Shibendu S. Ray; D. P. Vashishta; Jai Singh Parihar (Journal of the Indian Society of Remote Sensing, 2011)

A Spatial Database of Cropping System and its Characteristics to Aid Climate Change Impact Assessment Studies - Sushma Panigrahy; Shibendu Shankar Ray; K. R. Manjunath; P. S. Pandey; S. K. Sharma; Anil Sood; Manoj Yadav; P. C. Gupta; N. Kundu; Jai Singh Parihar (Journal of the Indian Society of Remote Sensing, 2011)

Contrasting Global Trends in Marine Fishery Status Obtained from Catches and from Stock Assessments - TREVOR A. BRANCH; OLAF P. JENSEN; DANIEL RICARD; YIMIN YE; RAY HILBORN (Conservation Biology, 2011)
There are differences in perception of the status of fisheries around the world that may partly stem from how data on trends in catches over time have been used. On the basis of catch trends, it has been suggested that about 70% of all stocks are overexploited due to unsustainable harvesting and 30% of all stocks have collapsed to

Modulation of transcription factor and metabolic pathway genes in response to water-deficit stress in rice - Swatismita Ray; Prasant K. Dansana; Jitender Giri; Priyanka Deveshwar; Rita Arora; Pinky Agarwal; Jitendra P. Khurana; Sanjay Kapoor; Akhilesh K. Tyagi (Functional & Integrative Genomics, 2011)

Stress-adapted extremophiles provide energy without interference with food production - Ray A. Bressan; Muppala P. Reddy; Suk Ho Chung; Dae Jin Yun; Lowell S. Hardin; Hans J. Bohnert (Food Security, 2011)

Deriving biomedical diagnostics from NMR spectroscopic data - Ian C. P. Smith; Ray L. Somorjai (Biophysical Reviews, 2011)

Bromus catharticus striate mosaic virus: a new mastrevirus infecting Bromus catharticus from Australia - James Hadfield; Darren P. Martin; Daisy Stainton; Simona Kraberger; Betty E. Owor; Dionne N. Shepherd; Francisco Lakay; Peter G. Markham; Ray S. Greber; Rob W. Briddon; Arvind Varsani (Archives of Virology, 2011)

Obesity and breast cancer: status of leptin and adiponectin in pathological processes - Michael E. Grossmann; Amitabha Ray; Katai J. Nkhata; Dmitry A. Malakhov; Olga P. Rogozina; Soner Dogan; Margot P. Cleary (Cancer and Metastasis Reviews, 2010)

Level of Heavy Metals in Some Edible Marine Fishes of Mangrove Dominated Tropical Estuarine Areas of Hooghly River, North East Coast of Bay of Bengal, India - T. K. De; M. De; S. Das; R. Ray; P. B. Ghosh (Bulletin of Environmental Contamination and Toxicology, 2010)

Feasibility Evaluation of Pressurized Irrigation in Canal Commands - Ramesh C. Srivastava; Sheelabhadra Mohanty; Ramlal B. Singandhuppe; Rajiv K. Mohanty; Madhu S. Behera; Lala I. P. Ray; Deepika Sahoo (Water Resources Management, 2010)

Peptides representing the specific variable regions but not the full porin proteins can be useful for antibody based diagnosis of typhoid fever - S. Kumar; S. Kapil; V. Gautam; S. K. Verma; P. Ray (Folia Microbiologica, 2010)

A novel species of mastrevirus (family Geminiviridae) isolated from Digitaria didactyla grass from Australia - Rob W. Briddon; Darren P. Martin; Betty E. Owor; Lara Donaldson; Peter G. Markham; Ray S. Greber; Arvind Varsani (Archives of Virology, 2010)

Assessment of the Jason-2 Extension to the TOPEX/Poseidon, Jason-1 Sea-Surface Height Time Series for Global Mean Sea Level Monitoring - B. D. Beckley; N. P. Zelensky; S. A. Holmes; F. G. Lemoine; R. D. Ray; G. T. Mitchum; S. D. Desai; S. T. Brown (Marine Geodesy, 2010)

Natural habitat change, commercial fishing, climate, and dispersal interact to restructure an Alaskan fish metacommunity - Peter A. H. Westley; Daniel E. Schindler; Thomas P. Quinn; Gregory T. Ruggerone; Ray Hilborn (Oecologia, 2010)

Shift in detrital sedimentation in the eastern Bay of Bengal during the late Quaternary - C. Prakash Babu; J. N. Pattan; K. Dutta; N. Basavaiah; G. V. Ravi Prasad; D. K. Ray; P. Govil (Journal of Earth System Science, 2010)

IRS-LISS-III and PAN data analysis for landslide susceptibility mapping using heuristic approach in active tectonic region of Himalaya - M. A. A. Patwary; P. K. Champati ray; Irshad Parvaiz (Journal of the Indian Society of Remote Sensing, 2009)

Impact of cropping pattern changes on the exploitation of water resources: A remote sensing and GIS approach - Anil Sood; B. U. Choudhury; S. S. Ray; S. K. Jalota; P. K. Sharma; Shushma Panigrahy (Journal of the Indian Society of Remote Sensing, 2009)

Epidemiological typing of clinical isolates of Achromobacter xylosoxidans: comparison of phenotypic and genotypic methods - M. Kaur; P. Ray; M. Bhatty; M. Sharma (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Targetable HPMA Copolymer–Aminohexylgeldanamycin Conjugates for Prostate Cancer Therapy - Mark P. Borgman; Abhijit Ray; Rohit B. Kolhatkar; Edward A. Sausville; Angelika M. Burger; Hamidreza Ghandehari (Pharmaceutical Research, 2009)

Adaptive response of equine intestinal Na+/glucose co-transporter (SGLT1) to an increase in dietary soluble carbohydrate - Jane Dyer; Miran Al-Rammahi; Louise Waterfall; Kieron S. H. Salmon; Ray J. Geor; Ludovic Bouré; G. Barrie Edwards; Christopher J. Proudman; Soraya P. Shirazi-Beechey (Pflügers Archiv - European Journal of Physiology, 2009)

Male-Produced Aggregation Pheromone of the Cerambycid Beetle Rosalia funebris - Ann M. Ray; Jocelyn G. Millar; J. Steven McElfresh; Ian P. Swift; James D. Barbour; Lawrence M. Hanks (Journal of Chemical Ecology, 2009)

Replication of association between ELAVL4 and Parkinson disease: the GenePD study - Anita L. DeStefano; Jeanne Latourelle; Mark F. Lew; Oksana Suchowersky; Christine Klein; Lawrence I. Golbe; Margery H. Mark; John H. Growdon; G. Fredrick Wooten; Ray Watts; Mark Guttman; Brad A. Racette; et al. (Human Genetics, 2008)

Influence of neotectonic activity on groundwater salinity and playa development in the Mendha river catchment, western India - V. S. Rathore; M. S. Nathawat; P. K. Champati Ray (International Journal of Remote Sensing, 2008)

Effect of timing of fungicide application on the development of Fusarium head blight and the accumulation of deoxynivalenol (DON) in winter wheat grain - S. Pirgozliev; R. Ray; S. Edwards; M. Hare; P. Jenkinson (Cereal Research Communications, 2008)

The Fruits of Tropical Plant Genomics - Andrew H. Paterson; Peter Felker; Stephen P. Hubbell; Ray Ming (Tropical Plant Biology, 2008)

Pharmacodynamic and pharmacokinetic characterisation of RBx 7796: a novel 5-lipoxygenase inhibitor - R. K. Shirumalla; P. Sharma; S. G. Dastidar; J. K. Paliwal; S. Kakar; B. Varshney; G. Singh Saini; V. Sattigeri; M. Salman; A. Ray (Inflammation Research, 2008)

Use of hyperspectral data to assess the effects of different nitrogen applications on a potato crop - Namrata Jain; Shibendu Shankar Ray; J. P. Singh; Sushma Panigrahy (Precision Agriculture, 2007)

Genome-wide identification of C2H2 zinc-finger gene family in rice and their phylogeny and expression analysis - Pinky Agarwal; Rita Arora; Swatismita Ray; Ashok K. Singh; Vijay P. Singh; Hiroshi Takatsuji; Sanjay Kapoor; Akhilesh K. Tyagi (Plant Molecular Biology, 2007)

Seismic microzonation of Dehradun City using geophysical and geotechnical characteristics in the upper 30 m of soil column - A. K. Mahajan; Siefko Slob; Rajiv Ranjan; Rob Sporry; P. K. Champati ray; Cees J. van Westen (Journal of Seismology, 2007)

Fuzzy-based method for landslide hazard assessment in active seismic zone of Himalaya - P. K. Champati ray; Suvarna Dimri; R. C. Lakhera; Santosh Sati (Landslides, 2007)

Identification and detection of genetic relatedness among important varieties of pea (Pisum sativum L.) grown in India - P. Ray Choudhury; Hasan Tanveer; G. P. Dixit (Genetica, 2007)

Polymerase Chain Reaction (PCR) Amplification of IS6110 Sequences to detect Mycobacterium tuberculosis Complex from Formalin-fixed Paraffin-embedded Tissues of Deer (Axis axis) - S. Sharma; G. P. Mallick; Rishendra Verma; S. K. Ray (Veterinary Research Communications, 2007)

Mapping of fault rupture of the 28 may 2004 iran earthquake (mw= 6.2) using satellite image - M. Sharifikia; C. S. Dubey; B. K. Sharma; M. Chaudhry; P. K. Champati Ray (Journal of the Indian Society of Remote Sensing, 2006)

Acetylcholinesterase activities in marine snail (Cronia contracta) as a biomarker of neurotoxic contaminants along the Goa coast, West coast of India - D. Gaitonde; A. Sarkar; S. Kaisary; C. D. Silva; C. Dias; D. P. Rao; D. Ray; R. Nagarajan; S. N. De Sousa; Subhodeep Sarker; D. Patill (Ecotoxicology, 2006)

Light-regulated overexpression of an Arabidopsis phytochrome A gene in rice alters plant architecture and increases grain yield - Ajay K. Garg; Ruairidh J. H. Sawers; Haiyang Wang; Ju-Kon Kim; Joseph M. Walker; Thomas P. Brutnell; Mandayam V. Parthasarathy; Richard D. Vierstra; Ray J. Wu (Planta, 2006)

Inhibition of Amazon Deforestation and Fire by Parks and Indigenous Lands - D. NEPSTAD; S. SCHWARTZMAN; B. BAMBERGER; M. SANTILLI; D. RAY; P. SCHLESINGER; P. LEFEBVRE; A. ALENCAR; E. PRINZ; GREG FISKE; ALICIA ROLLA (Conservation Biology, 2006)
Conservation scientists generally agree that many types of protected areas will be needed to protect tropical forests. But little is known of the comparative performance of inhabited and uninhabited reserves in slowing the most extreme form of forest disturbance: conversion to agriculture. We used satellite‐based maps of land cover and fire occurrence in the Brazilian Amazon to compare the performance of large (>10,000 ha) uninhabited (parks) and inhabited (indigenous lands, extractive reserves, and national forests) reserves. Reserves significantly reduced both deforestation and fire. Deforestation was 1.7 (extractive reserves) to 20 (parks) times higher along the outside versus the inside of the reserve perimeters and fire occurrence was 4 (indigenous lands) to 9 (national forests) times higher. No strong difference in the inhibition of deforestation (p= 0.11) or fire (p= 0.34) was found between parks and indigenous lands. However, uninhabited reserves tended to be located away from areas of high deforestation and burning rates. In contrast, indigenous lands were often created in response to frontier expansion, and many prevented deforestation completely despite high rates of deforestation along their boundaries. The inhibitory effect of indigenous lands on deforestation was strong after centuries of contact with the national society and was not correlated with indigenous population density. Indigenous lands occupy one‐fifth of the Brazilian Amazon—five times the area under protection in parks—and are currently the most important barrier to Amazon deforestation. As the protected‐area network expands from 36% to 41% of the Brazilian Amazon over the coming years, the greatest challenge will be successful reserve implementation in high‐risk areas of frontier expansion as indigenous lands are strengthened. This success will depend on a broad base of political support.

Marine and freshwater climatic factors affecting interannual variation in the timing of return migration to fresh water of sockeye salmon ( Oncorhynchus nerka ) - SAYRE HODGSON; THOMAS P. QUINN; RAY HILBORN; ROBERT C. FRANCIS; DONALD E. ROGERS (Fisheries Oceanography, 2006)
Interannual variation in the timing of the return migration to fresh water of adult sockeye salmon, Oncorhynchus nerka , from 46 populations throughout the species North American range was examined in a broad analysis of how timing patterns are affected by marine and freshwater conditions. Migration timing data (measured at various points along the migration, including just prior to freshwater entry, just after freshwater entry, and near the spawning grounds) were examined for correlations with sea‐surface temperatures (SST) prior to migration and to freshwater temperatures and flows during migration. Following a spring–summer period with warm SST, populations from southwestern Alaska tended to return early, Fraser River populations returned late, and populations from other regions showed no consistent patterns. Similarities between interannual timing of both nearby and distant populations indicated the presence of common or coincidental influences on timing. When riverine conditions related to timing, high flows and low temperatures were associated with late migrations, low flows and high temperatures were associated with early migrations. However, even counting stations at upriver locations showed correlations with SST. Notwithstanding some inconsistencies among the many populations examined and the indirect nature of the inferences, the results supported the hypotheses that (i) interannual variations in salmon distributions at sea reflect temperature conditions, and (ii) the date when salmon initiate homeward migration is a population‐specific trait, largely unaffected by the fish's location at sea.

A Quick appraisal of ground deformation in indian region due to the october 8, 2005 earthquake, Muzaffarabad, Pakistan - P. K. Champati ray; R. J. G. Perumal; V. C. Thakur; M. I. Bhat; M. A. Mallik; Vivek Kumar Singh; R. C. Lakhera (Journal of the Indian Society of Remote Sensing, 2005)

Molecular pathogenesis of Wilson disease: haplotype analysis, detection of prevalent mutations and genotype–phenotype correlation in Indian patients - A. Gupta; D. Aikath; R. Neogi; S. Datta; K. Basu; B. Maity; R. Trivedi; J. Ray; S. K. Das; P. K. Gangopadhyay; K. Ray (Human Genetics, 2005)

Accuracy assessment of InSAR derived input maps for landslide susceptibility analysis: a case study from the Swiss Alps - Lalan P. Singh; C. J. van Westen; P. K. Champati Ray; P. Pasquali (Landslides, 2005)

Use of GIS and remote sensing for crop diversification — a case study for Punjab state - S. S. Ray; Anil Sood; Gargi Das; Sushma Panigrahy; P. K. Sharma; J. S. Parihar (Journal of the Indian Society of Remote Sensing, 2005)

Trace element geochemistry of Amba Dongar carbonatite complex, India: Evidence for fractional crystallization and silicate-carbonate melt immiscibility - Jyotiranjan S. Ray; P. N. Shukla (Journal of Earth System Science, 2004)

Analysis of cropping pattern changes in Bathinda district, Punjab - Sushma Panigrahy; S. S. Ray; Anil Sood; L. B. Patel; P. K. Sharma; J. S. Parihar (Journal of the Indian Society of Remote Sensing, 2004)

Nonlinear Viscoelasticity in Rabbit Medial Collateral Ligament - Rittu V. Hingorani; Paolo P. Provenzano; Roderic S. Lakes; Anthony Escarcega; Ray Vanderby (Annals of Biomedical Engineering, 2004)

DDT and HCH Residues in Basmati Rice (Oryza sativa) Cultivated in Dehradun (India) - G. Suresh Babu; M. Farooq; R. S. Ray; P. C. Joshi; P. N. Viswanathan; R. K. Hans (Water, Air, & Soil Pollution, 2003)

Avenues for increasing salt tolerance of crops, and the role of physiologically based selection traits - Rana Munns; Shazia Husain; Anna Rita Rivelli; Richard A. James; A.G. Condon; Megan P. Lindsay; Evans S. Lagudah; Daniel P. Schachtman; Ray A. Hare (Plant and Soil, 2002)

Induction of cytochrome c release and apoptosis by Hck-SH3 domain-mediated signalling requires caspase-3 - V. Radha; Ch. Sudhakar; P. Ray; G. Swarup (Apoptosis, 2002)

Strategies for carbon acquisition in the red marine macroalga Coccotylus truncatus from the Baltic Sea - Snoeijs P.; Klenell M.; Choo K.; Comhaire I.; Ray S.; Pedersén M. (Marine Biology, 2002)

Protein A-activated macrophages induce apoptosis in Ehrlich's ascites carcinoma through a nitric oxide-dependent pathway - S. Chattopadhyay; T. Das; G. Sa; P. K. Ray (Apoptosis, 2002)

High iridium concentration of alkaline rocks of Deccan and implications to K/T boundary - P. N. Shukla; N. Bhandari; Anirban Das; A. D. Shukla; J. S. Ray (Journal of Earth System Science, 2001)

Identification and classification of aromatic rices based on DNA fingerprinting - P. Ray Choudhury; S. Kohli; K. Srinivasan; T. Mohapatra; R.P. Sharma (Euphytica, 2001)

Integrated commodity management methods with ca and/or fumigation - S. Prabhakaran; S. Ray; B. M. Schneider; R. E. Williams; P. Flinn; T. Phillips; D. Hagstrum; F. Arthur; J. Throne; R. N. Emery; R. A. Tassone; E. Kostas; et al. (Phytoparasitica, 2001)

Frequency of cytochrome P 450 3A4 variant genotype in transplant population and lack of association with cyclosporin clearance - L. P. Rivory; H. Qin; S. J. Clarke; J. Eris; G. Duggin; E. Ray; R. J. Trent; J. F. Bishop (European Journal of Clinical Pharmacology, 2000)

Antifungal activity of venenatine, an indole alkaloid isolated fromAlstonia venenata - U. P. Singh; B. K. Sarma; P. K. Mishra; A. B. Ray (Folia Microbiologica, 2000)

Physico-Chemical Quality of Drinking Water in Rohtas District of Bihar - D. Ray; R. Ravindar Rao; A. V. Bhoi; A. K. Biswas; A. K. Ganguly; P. B. Sanyal (Environmental Monitoring and Assessment, 2000)

Antifungal activity of Δ3-alstovenine, a plant alkaloid isolated fromAlstonia venenata - S. K. Singh; B. K. Sarma; J. S. Srivastava; U. P. Singh; A. B. Ray (Folia Microbiologica, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Contribution of NMDA and non-NMDA receptors to synaptic transmission from the brachium of the inferior colliculus to the medial subdivision of the medial geniculate nucleus in the rabbit - Tim J. Webber; Edward J. Green; Ray W. Winters; Neil Schneiderman; P. M. McCabe (Experimental Brain Research, 1999)

Rabies viruses infect primary cultures of murine, feline, and human microglia and astrocytes - N. B. Ray; C. Power; W. P. Lynch; L. C. Ewalt; D. L. Lodmell (Archives of Virology, 1997)

Genetic differentiation of populations of the common intertidal nemerteans Lineus ruber and Lineus viridis (Nemertea, Anopla) - Alex D. Rogers; John P. Thorpe; Ray Gibson; Jon L. Norenburg (Hydrobiologia, 1997)

Effect of methyl isocyanate (MIC) on rat erythrocytes - Deepa Agrawal; G. S. D. Gupta; J. S. Shukla; K. K. Dutta; P. K. Ray (Archives of Toxicology, 1990)

A study of nerve conduction velocity, late responses and neuromuscular synapse functions in organophosphate workers in India - U. K. Misra; D. Nag; W. A. Khan; P. K. Ray (Archives of Toxicology, 1988)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

Effects of copper on the sabellid polychaete,Eudistylia vancouveri: I. Concentration limits for copper accumulation - James S. Young; Ray L. Buschbom; James M. Gurtisen; Stephen P. Joyce (Archives of Environmental Contamination and Toxicology, 1979)

s of papers presented at the Forty-First annual meeting - Jay L. Haddock; Ray D. Jackson; W. O. Harrington; R. L. Olson; W. J. Weston; Mary L. Belote; W. J. Hooker; A. P. Benson; R. W. Hougas; S. J. Poloquin; R. W. Ross; G. V. C. Houghland; et al. (American Journal of Potato Research, 1958)

Summary of papers presented at The Potato Conference held at the Western Regional Research Laboratory, October 17 and 18, 1949 - R. Kunkel; W. T. Penzer; Paul P. Logan; Ray Kueneman; W. A. Scott (American Journal of Potato Research, 1950)